The Influence of Listening Team Learning (LTL) Model on Students’ Learning Outcome in Science - Sudirman Sudirman (Postgraduate, University of Mataram, 2023)
21st Century Learning requires teachers to choose learning models or strategies more creatively. This study aims to determine the differences in learning outcomes taught by the listening team model and conventional class models at SMPN 2 Maniangpajo. The design of this research is The Nonequivalent Posttest-Only Control Group Design. With the population of this study, all students in class VIII SMPN 2 Maniangpajo with a total of 70 students, and the sample was taken by purposive sampling obtained a sample of 47 students. The instruments used were learning achievement tests, and teacher and student observation sheets. The results of this study indicate that; 1) The learning outcomes of students taught using the listening team learning model have a moderate categorization with an average student learning outcome of 75.83. 2) The learning outcomes of students who are taught by the conventional model have a low categorization with an average score of students is 67.39. 3) There are significant differences in learning outcomes between the control and experimental classes. The listening team learning model is more effective than conventional learning models on student learning outcomes